Analysis of cell division in single clones of the Escherichia coli K-12 lexA mutant. - Howe, W E (1978)
The growth of clones of lexA mutant and lexA+ cells was analyzed. During normal growth lexA mutant clones frequently divided early, producing smaller newborn cells than the lexA+ clones. Some newborn cells in the lexA clones did not elongate or divide at all, a response that was never observed in the lexA+ clones. When starved for thymidine, most of the lexA mutant clones elongated and subsequently divided. The majority of lexA+ clones also elongated but did not divide. The above results suggest that one of the functions of the lexA+ gene is coordination of DNA repair with cell division.